Novel 4-substituted phenyl-2,2'-bichalcophenes and aza-analogs as antibacterial agents: a structural activity relationship - Hussin WA; Ismail MA; El-Sayed WM (Dove Medical Press, 2013)
Warda A Hussin,1 Mohamed A Ismail,2,3 Wael M El-Sayed2,41Al-Azhr University, Faculty of Science, Department of Botany and Microbiology, Cairo; 2King Faisal University, Faculty of Science, Departments of Biological Sciences and Chemistry, Al-Hufof, Ahsaa, KSA; 3Mansoura University, Faculty of Science, Department of Chemistry, Mansoura; 4University of Ain Shams, Faculty of Science, Department of Zoology, Abbassia, Cairo, EgyptAbstract: Antibiotic resistance is a major health problem; therefore, new antibacterial agents will need to be continuously developed. A series of novel bichalcophenes has been tested and found to have antimicrobial activity against selected bacteria. Due to the promising antimicrobial effects of these 4-substituted phenyl bichalcophene derivatives, the study reported here was launched to examine the interaction between novel bichalcophenes and tetracycline. The minimum inhibitory concentration values for all bichalcophenes were between 8 and 64 µM. Many of the bichalcophenes had synergistic activity that increased the inhibitory effect of tetracycline against bacterial growth, as indicated by the fractional inhibitory concentration index. The post-antibiotic effects of the novel bichalcophenes were determined. Many bichalcophenes were able to elongate the period required for bacteria to recover and grow after a brief exposure to tetracycline. Escherichia coli did not develop resistance to many bichalcophenes over a period of 7 days. A structural activity relationship could be characterized, as monocationic derivatives were more active than the corresponding mononitriles. The presence of a pyridyl group and/or furan ring reduced the activity, while the presence of a phenyl or thiophene ring enhanced the antibacterial activity. Our results suggest that bichalcophenes could be useful to elevate the shelf life of many antibiotics.Keywords: synergic interaction, fractional inhibitory concentration, post-antibiotic effect, resistant variants